A ANALISIS PROSES PEMBUATAN BATIK KARAWO - Sinta Nuria Mariono; Hasdiana Saleh; Ulin Naini (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study aims to create a textile works that combine Batik techniques and Karawo embroidery which are then called Karawo embroidery. Karawo embroidery has an artistic form and also contributes to cultural preservation because it uses typical Gorontalo motifs. Through the process of making Karawo Batik, a new visual appearance can be created in textile craft works that maintain traditional values and continue to adapt to the times. This study uses a qualitative method with a descriptive approach. The results of this study indicate that process of making quality textile products. The stages of making Karawo Batik are 1) Selecting fabric, 2) Making motifs, 3) The canting process, 4) The process of slicing and pulling theads, 5) Soaking fabric in TRO, 6) Coloring, 7) Pelorodan, 8) And embroidering, the manufacturing process has gone quite well. In addition, the resulting Karawo has its own uniqueness through distinctive motifs that reflect the combination of Batik techniques and Karawo embroidery as a form of preserving local wisdom.